Role of shared identity and agency trust in online voting among Finnish citizens - Farooq, Ali (Elsevier Ltd, 2025)
This study examined the impact of shared identity and agency trust, governmental vs. third party, on Finnish citizens' intention to vote online. Using the integrated model of shared identity and trust as a theoretical lens, a within-subject quasi-experiment was conducted to understand the impact of agency trust on intention to vote online. The model was tested using data from 248 Finnish citizens using PLS-SEM. We found that citizens’ perceptions of shared identity with online voting agencies significantly contribute to agency trust. This trust in agencies, then directly and indirectly through perceived usefulness, affects online voting intention. Perceived usefulness directly and perceived ease of use indirectly increase the intention to vote online. However, the perceived usefulness of online voting is contingent upon the voting administering agency being the government. This study contributes to the understanding of agency trust in online voting adoption in the Finnish context and highlights the role of shared identity in building citizen trust in online voting. It also emphasizes the effect of voting agency type on the perceived usefulness of online voting.